Mental Health Impacts of the COVID-19 Pandemic on International University Students, Related Stressors, and Coping Strategies - Lai, Agnes Yuen-kwan; Lee, Letitia; Wang, Man-ping; Feng, Yibin; Lai, Theresa Tze-kwan; Ho, Lai-ming; Lam, Veronica Suk-fun; Ip, Mary Sau-man; Lam, Tai-hing (Frontiers in Psychiatry, 2020)
Background:The COVID-19 pandemic has disrupted university teaching globally. The mental health impacts on international university students have been overlooked. Aims:This study examined the differences in COVID-19-related stressors and mental health impacts between international university students studying in the UK or US who returned to their home country or region(returnees) and those who stayed in their institution country ](stayers); and identified COVID-19-related stressors and coping strategies that were predictors of mental health. Method: An online questionnaire survey was conducted from 28 April through 12 May 2020 using an exponential, non-discriminative snowball sampling strategy. (Registered at National Institutes of Health: NCT04365361). Results:124 full-time international university students (36.3% male) were included. 75.8% had returned to their home country or region for reasons related to COVID-19. 77.4% were pursuing a bachelor’s programme and 53.2% were in programmes with practicum component. 84.7% of all students had moderate to high perceived stress, 12.1% had moderate to severe symptoms of anxiety and depression, and 17.7% had moderate to severe symptoms of insomnia Compared with returnees, stayers had significantly higher stress from COVID-19-related stressors such as personal health and lack of social support (Cohen’s d: 0.57-1.11), higher perceived stress (PSS-10) [22.6 ± 6.2 versus 19.1 ± 6.1, ß (95% confidence interval (CI)): 4.039 (0.816, 7.261), Cohen’s d: 0.52], and more severe insomnia symptoms (ISI) [11.8 ± 6.1 versus 7.6 ± 5.2, ß (95% CI): 3.087 (0.262, 5.912), Cohen’s d: 0.45], with moderate to large effect sizes. Compared with males, females reported significantly higher stress from uncertainties about academic programme (Cohen’s d: 0.45) with a small effect size. In the total sample, stress related to academics (e.g., personal attainment, uncertainties about academic programme, and changes in teaching/learning format), health (including personal health and health of family and friends), availability of reliable COVID-19-related information, and lack of social support predicted more negative mental health impacts. Resilience, positive thinking, and exercise were predictors of less severe mental health impacts. Conclusions:Stayers experienced more adverse mental health impacts than returnees. We call on educators and mental health professionals to provide appropriate support for international students, particularly the stayers, during the pandemic.